Positional differences in the micro- and ultra-structural variations of ray parenchyma cells during the transformation from sapwood to heartwood - Yin, Lijuan; Ma, Lingyu; Jiang, Xiaomei; Zhang, Yonggang; Wei, Yupei; Cao, Yuan; Yao, Lihong; Guo, Juan (Frontiers in Plant Science, 2024)
Ray parenchyma cells are involved in the initiation of heartwood formation. The position within a ray influences the timing of ray parenchyma cell differentiation and function, however little information concerns the positional influence on cellular changes of ray parenchyma cells from sapwood and heartwood. In this study, radial variations in morphology, size, and ultrastructure of ray parenchyma cells were studied by combined transmission electron microscopy and optical microscopy. Results showed that cellular traits of ray parenchyma cells in Populus tomentosa were all affected by both radial position in the secondary xylem and position within a ray. Specifically, radial variations in cellular traits were more evident in isolation cells, which were not adjacent to vessel elements. Both cell length and cell width/length ratio of isolation cells were bigger than contact cells, which were contacted with adjacent vessel elements via pits. Moreover, the secondary wall thickening and lignification of contact cells developed in the current-year xylem, much earlier than isolation cells. Secondary walls in contact cells were in a polylamellate structure with a protective layer on the inner side. No alteration in the ultrastructure of contact cells occurred in the sapwoodheartwood transition zone, except that most contact cells died. By contrast, in the transition zone, isolation cells still lived. A thin secondary wall began to deposit on the thick primary wall of isolation cells, being characteristic of two isotropic layers on the inner side of the primary wall and secondary wall respectively. Meanwhile, starch grains in isolation cells were depleted, and dark polyphenolic droplets lost their spherical shape and flowed together. Furthermore, intercellular spaces of isolation cells became densified in the transition zone. Overall, cellular changes suggested that the positional information of ray parenchyma cells appeared to be an important factor in the transformation from sapwood to heartwood. Unlike contact cells, isolation cells were more elongated, specialized in radial transport, had the delayed formation of secondary walls, and were involved in the synthesis of heartwood substances. Our result promotes the elucidation of the involvement of xylem rays in heartwood formation.